Case studies in open access publishing. Number one. The Electronic Journal of Information Technology in Construction (ITcon): an open access journal using an un-paid, volunteer-based organization. - Bo-Christer Bjoerk; Ziga Turk (Information Research: An International Electronic Journal)
This case study is based on the experiences with the Electronic Journal of Information Technology in Construction (ITcon), founded in 1995. This journal is an example of a particular category of open access journals, which use neither author charges nor subscriptions to finance their operations, but rely largely on unpaid voluntary work in the spirit of the open source movement. The journal has, after some initial struggle, survived its first decade and is now established as one of half-a-dozen peer reviewed journals in its field. The journal publishes articles as they become ready, but creates virtual issues through alerting messages to “subscribers”. It has also started to publish special issues, since this helps to attract submissions, and also helps in sharing the work-load of review management. From the start the journal adopted a rather traditional layout of the articles. After the first few years the HTML version was dropped and papers are only published in PDF format. The journal has recently been benchmarked against the competing journals in its field. Its acceptance rate of 53% is slightly higher and its average turnaround time of seven months almost a year faster compared to those journals in the sample for which data could be obtained. The server log files for the past three years have also been studied. Our overall experience demonstrates that it is possible to publish this type of OA journal, with a yearly publishing volume equal to a quarterly journal and involving the processing of some fifty submissions a year, using a networked volunteer-based organization.